Towards a Visualisation Process for Ontology-Based Conceptual Modelling - Braun, Germán (2016)
Visualisation of models by means of graphical representations plays a critical role in ontology development and maintenance. Tools are essential in understanding models and generating explicit, better usable and communicable knowledge. In this respect, we introduce a knowledge visualisation process for the integration of visual representations, logic-based reasoning and metamodelling for interoperability of languages. The intention behind this work is to offer a trade-off between these dimensions in the context of a semantics-aware tool. We provide means to stimulate interest in such tools for designing both conceptual models and ontologies based on the effectiveness of graphical modelling languages for expressing them.